Simplified formulations for the determination of rotational spring constants in rigid spread footings resting on tensionless soil - Girgin, Konuralp (Journal of Civil Engineering and Management, 2017)
In spread footings, the rotational spring constants, which represent the soil-structure interaction, play an important role in the structural analysis and design. To assign the behaviour of soil, which is generally represented via Winkler-type tensionless springs, necessitates time consuming iterative computing procedures in practice. In this study, a straightforward approach is proposed for the soil-structure interaction of rigid spread footings especially subjected to excessive eccentric loading. By considering the uplift of footing, the rotational spring constants of those type footings under axial load and biaxial bending are easily attained through the proposed simplified formulations. Since these formulations enable manual calculation, iterative computer efforts are not required. The formulations under consideration can be applicable to symmetric and non-symmetric rigid spread footings. The numerical results of this study are verified with SAP2000.